Postural Control and Psychophysical State Following of Flight Simulator Session in Novice Pilots - Polak, Ewa; Ślugaj, Remigiusz; Gardzińska, Adrianna (Frontiers in Public Health, 2022)
Flight simulators can cause side effects usually called simulator sickness. Scientific research proves that postural instability can be an indicator of the occurrence of simulator sickness symptoms. This study aims to assess changes of postural control and psychophysical state in novice pilots following 2-h exposure to simulator conditions. The postural sway was quantified based on variables describing the displacement of the Center of Pressure (COP) generated in a quiet stance with eyes open (EO) and closed (EC). The psychophysical state was assessed using the Simulator Sickness Questionnaire (SSQ). The research was carried out in a group of 24 novice pilots who performed procedural and emergency flight exercises in the simulator at Instrument Meteorological Conditions. Each subject was examined twice: immediately before the simulator session (pre-exposure test), and just after the session (post-exposure test). The differences in postural stability between pre- and post-exposure to simulator conditions were assessed based on the normalized Romberg quotients, calculated for individual variables. The lower median values of all Romberg quotients confirmed the decreasing difference between the measures with eyes open and with eyes closed in the post-exposure tests. After the flight simulator session in both measurements (EO and EC) the values of the length of sway path (SP), the mean amplitude (MA), the sway area (SA) have changed. The visual contribution to postural sway control was reduced. The median values for all SSQ scores (total, nausea, oculomotor, and disorientation scales) were significantly higher in post-exposure tests. The largest increase was noted in the oculomotor SSQ scores (from 7.6 ± 7.6 to 37.9 ± 26.5). Over 50% of pilots participating in this study expressed symptoms typical of simulator sickness connected with visual induction: fatigue, eyestrain, difficulty focusing and difficulty concentrating. The severity of oculomotor and disorientation symptoms were rated as moderate (total SSQ score of more than 25 and <60). This study concludes that changes noted in the postural control and psychophysical state of the studied pilots after exposure to the flight simulator confirm the occurrence of the simulator sickness symptoms. Although, we did not find significant correlation of postural stability with SSQ scores.